N-doping and oxidation of carbon nanotubes and jellyfish-like graphene nanoflakes through the prism of Raman spectroscopy - Chernyak, Sergei A. (2021)
Present work demonstrates the differences between the structure and surface transformations of carbon nanotubes (CNTs) and graphene nanoflakes with small particle size (GNFs) under oxidation and N-doping using Raman spectra processing. Jellyfish-like GNFs are rather new material that differs from the commonly known graphene nanoflakes by rounded edges and small size of particles (<50 nm). This material is promising in electrochemistry due to its high specific capacitance. It was found that, despite the graphene nature of both CNTs and GNFs, their Raman spectra change differently under oxidation and N-doping because of the different growth mechanisms of CNTs and GNFs, strong curvature of carbon layers in CNTs, and a large number of edge carbon atoms in GNFs.